Use of the sterile insect technique in New Zealand Benefits and constraints - Horner, R.M.; Walker, J.T.S.; Rogers, D.J.; Lo, P.L.; Suckling, D.M. (New Zealand Plant Protection, 2016)
The sterile insect technique (SIT) is increasingly being evaluated as a potential complementary strategy for pest suppression or elimination New Zealands export fruit sector has an imperative to meet strict international phytosanitary requirements together with increasing market demand for residuefree produce SIT is a pestspecific method of insect control that can complement current Integrated Pest Management (IPM) strategies Successful SIT presents significant challenges the target pest must be a good candidate for suppression and strong stakeholder and community commitment is required to achieve and maintain suppression until areawide elimination is achieved Emerging sterilisation technologies and refinement of existing methods are making this technology progressively more efficient and costeffective This study reviewed the advantages of including SIT in an IPM programme and described the first use of codling moth SIT in New Zealand A pilot programme is currently underway to evaluate its potential to achieve local elimination of codling moth in Central Hawkes Bay apple orchards